Glass Icons in Transylvania (Romania) and the Craft of Painting Them as Cultural Heritage Resources - Daniela Sorea; Ionuț Mihai Popescu (Heritage, 2022)
The craft of painting icons on glass developed in the 17th century in Transylvania (Romania) following the spread of the news about the wooden icon of the weeping Mother of God in the church of Nicula. This news turned Nicula into a pilgrimage centre, and requests for reproductions of the icon led to the locals becoming glass painters. Because of the surplus of icons, some of the Nicula painters set up new icon-painting centres along the road to Brașov (to the south) and the other main trade routes of Transylvania. In order to highlight the potential for sustainable development associated with this craft and to stimulate the painting of icons in the traditional way, we conducted documentary research on the subject of icons on glass. This research revealed the local peculiarities of the icon painters’ workshops and their importance to the identity of the Romanian peasants in Transylvania. We also conducted a participatory observation carried out in Brasov, which revealed that the iconography courses in popular schools of arts and crafts were both a viable way of managing the relationship with the iconographic tradition and a means to capitalize on religious painting on glass as a cultural heritage resource. The research highlighted the way in which, to preserve the traditional dimension of the craft, it is useful to encourage students to use anonymous glass icons as models and to have limited involvement in model restoration.